Use of the Problem Based Learning (PBL) Learning Model To Improve Student Learning Outcomes in Subjects Social Sciences Class IV at SD Negeri 064967 Medan Timur - Novita, Novita; Elfrianto, Elfrianto (Holistic Science, 2024)
Problem based learning (PBL) is a learning model that trains and develops the ability to solve problems that are otiented toward autehentic problems from student lives (Pulu Suardanan. 2019). The aim of this research is to improve students social studies learning out comes by using. The Problem Based Learning (PBL). The main Problem studied in this research is the learning out comes of students in class IV social student at SD Negeri 064967 Medan. The method used in this research is classroom action research (PTK) which consist of two cyscles consistof two meetings, the isntruments used are observation sheets, field notes and learning outcomes test (Post Test)